Historical Analysis of the Changing Meaning of Bengkulu Tabot Tradition - Agus Sapriansa; Arditya Prayogi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2023)
The existence of multiple meanings of the implementation of the Bengkulu Tabot tradition is the main background for writing this article. This meaning implements the Bengkulu Tabot ceremony tradition and changes its function. Thus this article aims to reveal the dynamics of changing the meaning of the Tabot tradition historically. This article is a qualitative research using historical research methods including heuristics, verification, interpretation, and historiography. From the results of the analysis, it is known that at first, the Bengkulu Tabot tradition had a sacred-magical value which in its implementation was closely related to the entry of the Syi'ah-Punjab understanding into the Bengkulu region. This form of implementation of the Bengkulu Tabot tradition is specially recorded in the manuscript of the Story of Tabot which has a sacred dimension. However, along with the times, the implementation of the Tabot tradition then changed its value to become profane in the form of the Bengkulu Tabot festival. The implementation of this festival takes on the identity of Tabot Pembangunan which was introduced by the Bengkulu Government. This condition resulted in the emergence of a discourse related to the legality of identity in the Tabot tradition in Bengkulu.